Study of air flow in a propulsion laboratory fume cabinet [electronic resource] - 261022 Billy Laja Dickson (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2008